2018
DOI: 10.1007/s10479-018-2889-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of food security based on DEA method: a case study of Heihe River Basin

Abstract: As long as it is competitive worldwide the Agribusiness in Colombia is called to become a strategic axis for the economic development of the regions and national productivity. The agribusiness sector of specific processed foods in oil companies and bakery companies were declared by Productive Colombia 2 as sectors with world-class potential for its high valueadded component.This project aims to become a tool to support the strategic decision-making process in this type of companies. The purpose it was to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Productivity also heavily depends on the climate conditions, and thus a change in climate to higher temperatures or frequent extreme weather conditions can have a major impact on productivity. There is a need to investigate the impact of possible climate change scenarios on food production and food security (Zhan et al., 2020). We next focus on emerging themes and opportunities for future research.…”
Section: Operational Efficiency In Farmingmentioning
confidence: 99%
“…Productivity also heavily depends on the climate conditions, and thus a change in climate to higher temperatures or frequent extreme weather conditions can have a major impact on productivity. There is a need to investigate the impact of possible climate change scenarios on food production and food security (Zhan et al., 2020). We next focus on emerging themes and opportunities for future research.…”
Section: Operational Efficiency In Farmingmentioning
confidence: 99%
“…Given that, the particular approach has been widely adopted in related studies of TFP. Most scholars employing the DEA-Malmquist productivity index to study TFP in China's agriculture concluded that agricultural TFP was mainly driven by TC and that the decrease of EC was in sync with that of TC for most parts of China [13,14]. e paper, therefore, attempts to employ the DEA-Malmquist indexbased approach to decompose agricultural TFP of Hubei into TC and EC.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among others, the study contributes by employing a big data sample that closely represents the population. Taking the Heihe River Basin (HRB) as a case study area and using DEA and the Malmquist index, Zhan et al (2020) analysed the agricultural production efficiency in the HRB and further aimed to identify what was the role played by big data in the assessment of food security. developed a new methodology for rural transportation management which takes into consideration both the equity and cost factors under multiple objectives.…”
Section: Herranz Et Al (2017) Used Principal Component Analysis Dea and Artificialmentioning
confidence: 99%